2017
DOI: 10.1093/jxb/erx199
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous sieve element proteins are able to limit phloem mass flow, but not phytoplasma spread

Abstract: The lack of correlation between sieve element filament formation, sieve element occlusion, and phytoplasma titre hints at an unknown role for filamentous sieve element proteins in plant defence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 74 publications
(131 reference statements)
2
57
0
Order By: Relevance
“…Recently, we demonstrated that phloem flow was limited in Chrysanthemum yellows (CY) phytoplasmainfected wild-type plants, but not in healthy wild-type and neither in healthy and infected Atseor mutant lines. Moreover, phloem flow reduction and CY phytoplasma dissemination did not seem to be correlated, since the phytoplasma titre was significantly lower in the mutant line Atseor1ko than in wild-type plants (95.55E+06 and 600.87E+06 phytoplasma genome units mg -1 of leaf sample, respectively) 12 . This phenomenon could be explained by the assumption that phytoplasmas are not passively translocated by phloem mass flow and, hence, do not strictly depend on mass flow for their spread 13 .…”
Section: Sieve-tube Constriction Does Not Limit Phytoplasma Spreadmentioning
confidence: 92%
“…Recently, we demonstrated that phloem flow was limited in Chrysanthemum yellows (CY) phytoplasmainfected wild-type plants, but not in healthy wild-type and neither in healthy and infected Atseor mutant lines. Moreover, phloem flow reduction and CY phytoplasma dissemination did not seem to be correlated, since the phytoplasma titre was significantly lower in the mutant line Atseor1ko than in wild-type plants (95.55E+06 and 600.87E+06 phytoplasma genome units mg -1 of leaf sample, respectively) 12 . This phenomenon could be explained by the assumption that phytoplasmas are not passively translocated by phloem mass flow and, hence, do not strictly depend on mass flow for their spread 13 .…”
Section: Sieve-tube Constriction Does Not Limit Phytoplasma Spreadmentioning
confidence: 92%
“…Sieve-element protein filaments aggregate in sieve tubes of wild-type Arabidopsis line from the early stage of infection onward. We previously demonstrated that SE protein filaments play a role in the plant response to phytoplasma infection, even in the absence of genes that are considered necessary for their formation in healthy plants 8,9 . Nevertheless, the picture drawn at that time did not explain whether SE protein filaments per se are involved in some defence mechanisms, such as early pathogen containment.…”
Section: Discussionmentioning
confidence: 99%
“…For phytoplasma detection, the 3 insects used on each Arabidopsis were pooled, to obtain 72 pools per condition. Total DNA was extracted as described 79 and the presence of phytoplasmas in each pool was assayed by conventional PCR using the primer pair R16F2/R2, as described by Pagliari and co-authors 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEO proteins are widespread and likely ubiquitous among dicotyledon plants (Rüping et al, 2010;Ernst et al, 2011). In most dicotyledonous plants, SEO proteins are believed to be filamentous and confined to a parietal position in translocating sieve elements (Ehlers et al, 2000;Froleich et al, 2011;Anstead et al, 2012;Pagliari et al, 2017). Upon damage, they are released into the lumen of the sieve element and are carried to the downstream sieve plate where they occlude the sieve pores (Ehlers et al, 2000;Ernst et al, 2012;Jekat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%